2021
DOI: 10.1136/jim-2020-001693
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Health Clinicians Endorse Stellate Ganglion Block as a Valuable Intervention in the Treatment of Trauma-Related Disorders

Abstract: The stellate ganglion block (SGB) procedure has been used successfully for over 10 years to treat post-traumatic stress symptoms in thousands of US military service members, civilians, and veterans in select hospitals in Europe and North America. Primarily through targeting the autonomic nervous system, the SGB procedure serves as an invaluable adjunct to trauma-focused psychotherapy. Without published best practices for emerging therapies, clinicians are left on their own to determine how best to apply new tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…For example, in addition to its role in calcium and bone metabolism, Vitamin D is critical to numerous autocrine, paracrine, and endocrine processes which modulate the hypothalamic-pituitary-adrenal axis, a complex hormonal system that is implicated in several psychiatric disorders like PTSD, MDD, and GAD [ 42 - 43 ]. Further, as the vagus nerve, a major nerve of the parasympathetic nervous system, innervates the intestinal system and produces anxiolytic or anxiogenic signals in response to certain pathogenic bacteria in the gut microbiome, evidence suggests that the gut microbiome may influence brain function [ 44 - 45 ]. Numerous studies have demonstrated that patients with depression have distinct microbiota signatures when compared with healthy controls, highlighting a potential relationship between the gut microbiome and abnormal brain function [ 46 ].…”
Section: Reviewmentioning
confidence: 99%
“…For example, in addition to its role in calcium and bone metabolism, Vitamin D is critical to numerous autocrine, paracrine, and endocrine processes which modulate the hypothalamic-pituitary-adrenal axis, a complex hormonal system that is implicated in several psychiatric disorders like PTSD, MDD, and GAD [ 42 - 43 ]. Further, as the vagus nerve, a major nerve of the parasympathetic nervous system, innervates the intestinal system and produces anxiolytic or anxiogenic signals in response to certain pathogenic bacteria in the gut microbiome, evidence suggests that the gut microbiome may influence brain function [ 44 - 45 ]. Numerous studies have demonstrated that patients with depression have distinct microbiota signatures when compared with healthy controls, highlighting a potential relationship between the gut microbiome and abnormal brain function [ 46 ].…”
Section: Reviewmentioning
confidence: 99%
“…Of those surveyed, 100% of clinicians characterized SGB as "Very Beneficial" or "Somewhat Beneficial," and 95% would recommend SGB to a colleague. 46 Thus, both patients and clinicians report generally positive experiences with SGB.…”
Section: Published Studiesmentioning
confidence: 99%
“…An SGB is a therapeutic strategy that can effectively regulate the stability of autonomic nervous, endocrine, and immune functions. An SGB protects the lungs through multiple pathways, such as inhibition of systemic inflammation, reduction of oxidative stress, [6] inhibition of apoptosis at the site of injury, [7] and modulation of pulmonary vasomotor activity. [8] However, no specific effects of the SGB have been reported in patients undergoing mechanical ventilation under clinical anesthesia.…”
Section: This Study Was Supported By a Grant From The Xinjiang Key La...mentioning
confidence: 99%